Development of process system for treatment of oil contaminated soils & sludges in the Niger Delta - Chukwuogo, C. E. B. (Cranfield University, 2005)
One of the major problems with process equipment/systems set up in Nigeria is the lack of sustained productivity, arising from the basic inappropriateness of such equipment/system to the technological level of the country. The pollutions arising from the Oil & Gas exploitation activities in the Niger Delta were highlighted. In this project, the development of a unique processing system capable of advantageously treating oil contaminated soils and sludges in the Niger Delta was undertaken. The specific constraints in that terrain are outlined. The treatment systems that are currently available worldwide which are applicable to the Niger Delta have various limitations. The system designed had to be able to overcome all those limitations. Design superiority and success in the market place being two desirable aspects of a product, the project focused on the possibility of processing the contaminated materials at a higher rate without compromising quality. The need to generate its own fuel for firing burners and diesel for firing the electricity generators was one of the main drivers for the project. The system developed was tested at pilot level for effectiveness in those key areas. A totally energy-independent process has thus been created, which generates energy for the material being treated. This will guaranty the success in the market place in treating the contaminated sites of the Niger Delta, at commercial rates that are about a third of the current rates in the region. It is also estimated that capital and operating costs will be less than half of foreign built units, which ensure faster attainment of breakeven point. The future work that could be undertaken in this area include the field trials of a mini-sized processing unit and the eventual translation of processing parameters and information into a life size, commercial system able treat materials as required.